Study of Electronic Speed Control Strategies for a Fixed Battery, Motor and Propeller Aircraft Propulsion Set - Zombori, Viktor (2022)
A study of an electrical propulsion system with two propeller options and a fixed battery and motor was performed, in the context of the participation of the AERO@UBI team in the Air Cargo Challenge 2021/2022. The goals were to maximize the thrust generated by the setup, specially at high relative wind speed, by means of adopting the best motor control strategy and to select the better propeller for this purpose. Two electronic speed controllers (ESCs) were selected: the Castle Creations Phoenix ICE 75, that performs trapezoidal commutation, and a Team Triforce A50S, which makes use of field-oriented control (FOC). Both were tested under static condition and with relative wind, using a static thrust stand and an experimental setup in a wind tunnel, respectively. These tests allowed to understand the influence on the generated thrust and drawn current of different settings that are implemented on the controllers, such as motor timing and pulse-width modulation (PWM) rate, as well as various magnitudes of field weakening. The obtained results were very positive: under static conditions, FOC with field weakening allowed to increase the generated static thrust by more than 10% relative to the best value obtained with trapezoidal commutation. This difference was amplified even more with increasing relative wind speed.